(untitled) (REMUNOM, 2026)
The municipality of Ipameri, located in the southern mesoregion of Goiás State, stands out due to its relevance in the agricultural sector, with strong potential for grain production and several other crops. However, irregular rainfall distribution and prolonged drought periods represent significant challenges to agriculture, especially for rainfed cropping systems. In this context, this study aimed to perform a climatological water balance and the Köppen and Thornthwaite and Mather climate classifications for the municipality of Ipameri, Goiás State, covering the period from 1991 to 2020, using climatological data provided by the National Institute of Meteorology (INMET). The total annual precipitation was 1,481.8 mm, with a well-defined seasonal pattern: 93.7% of the rainfall is concentrated between November and March (rainy season), while the months from May to September present the lowest accumulations (dry season). The mean annual air temperature was 22.9 °C, with October being the warmest month (25.1 °C) and June and July the coldest (19.8 °C and 19.9 °C, respectively). According to the Köppen climate classification, the climate is classified as tropical with a dry winter (Aw), whereas the Thornthwaite and Mather classification characterized it as humid megathermal with moderate water deficiency in winter (B1 w A’ b’4). The results highlight the importance of agricultural planning and the adoption of sustainable irrigation practices to mitigate the impacts of the dry season, ensuring water security and crop productivity. This study provides support for efficient water resource management and for the development of adaptive strategies in response to climatic variability in the region.